Ethical Fintech is a New Way of Banking - Rina Arum Prastyanti; Rezi Rezi; Istiyawati Rahayu (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The adoption of Financial Technology (FinTech) and digital banking services has revolutionized the financial industry, providing convenience, accessibility, and cost-effective solutions to users. However, along with its benefits, the widespread use of FinTech has also raised concerns regarding privacy, security, consumer protection, ethical considerations, and regulatory compliance. This paper aims to explore the ethical dimensions of FinTech adoption and the potential negative consequences associated with it. Drawing on qualitative research methods, including interviews and document analysis, the study investigates issues such as consumer privacy, data breaches, trust, financial integrity, adoption barriers, and ethical controversies in the diffusion of FinTech. The findings highlight the importance of addressing these ethical concerns to restore digital ethics in the fintech industry and ensure principles such as fairness, transparency, accountability, and access in technology are realized. The paper concludes by emphasizing the need for a balance between technological innovation and ethical practices to create a sustainable and responsible future for FinTech and digital banking.